Priming with Secreted Glycoprotein G of Respiratory Syncytial Virus (RSV) Augments Interleukin-5 Production and Tissue Eosinophilia after RSV Challenge - Johnson, Teresa R. (American Society for Microbiology, 1998)
The respiratory syncytial virus (RSV) G glycoprotein promotes differentiation of type 2 CD4(+) T lymphocytes and induces an eosinophilic response in lungs of RSV-infected mice. A unique feature of G is that a second initiation codon in the transmembrane region of the glycoprotein results in secretion of soluble protein from infected cells. Recombinant vaccinia viruses that express wild-type G (vvWT G), only secreted G (vvM48), or only membrane-anchored G (vvM48I) were used to define the influence of G priming on immunopathogenesis. Mice immunized with vvM48 had more severe illness following RSV challenge than did mice primed with vvWT G or vvM48I. Coadministration of purified G during priming with the construct expressing membrane-anchored G shifted immune responses following RSV challenge to a more Th2-like response. This was characterized by increased interleukin-5 in lung supernatants and an increase in G-specific immunoglobulin G1 antibodies. Eosinophils were present in the infiltrate of all mice primed with G-containing vectors but were greatest in mice primed with regimens including secreted G. These data suggest the form of G protein available for initial antigen processing and presentation is an important factor in promoting Th2-like immune responses, including the induction of lung eosinophilia. The ability of RSV to secrete G protein may therefore represent a viral strategy for immunomodulation and be a key determinant of disease pathogenesis.